USM STRENGTHENS COLLABORATION WITH INSTITUT TEKNOLOGI BANDUNG - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BANDUNG, 15 October 2015 – The Vice-Chancellor of Universiti Sains Malaysia (USM) Professor Dato' Dr. Omar Osman recently met the Rector of Institut Teknologi Bandung (Bandung Institute of Technology/ITB) Indonesia, Profesor Kadarsah Suryadi to strengthen existing ties between the two institutions.